The Impact of Parenting Styles, Peers, and Teachers on Internet Usage and Addiction among Secondary School Students in Sekolah Menengah Kebangsaan Ibrahim - Azizi Yahaya (Human Resource Management Academic Research Society, 2022)
The internet usage and addiction of the students has been the area of concern since internet has been used in teaching and learning approach in this new era. Therefore, this study was conducted to identify the influences of parenting styles, peers, and teachers on internet usage and addiction among secondary school students in Johor, Malaysia. This research was carried out using a quantitative method in which 200 students from ages 13 to 17 were selected randomly to take part in answering the survey form. The number of respondents was determined by using Krejcie and Morgan (1970) method of sampling. The survey form was divided into five parts, Part A demography, Part B internet usage and addiction, Part C influences of parenting styles, Part D influences of peers, and Part E influences of teachers. The reliability and validity for each of the variables were measured using Cronbach’s alpha where all four variables are said to have α > 0.5. Part B with (α= 0.883), Part C (α= 0.851), Part D (α= 0.744), and Part E with (α= 0.695). Based on the findings, it has been identified that the most dominant factor of parenting style is the permissive style as it has the highest value of mean, 3.72 compared to authoritarian (3.32), authoritative (3.52), and neglectful (3.25). This study showed that the involvement level of peers is moderate with the mean value of 3.42 and as well as teachers’ involvement (3.24). While parenting styles, peers, and teachers are good predictors of internet usage and addiction among secondary school students. with the value F (2,97) = 35.24 P<0.05. These three independent variables, which are parenting styles, peers, and teachers predicted internet usage and addiction among secondary school students. Given this, all three variables (e.g., parenting styles, and peers and teachers) have an impact on students' addiction to the internet. The implications of the study where it could raise parents’ and public awareness and understanding to minimize internet addiction among the younger generation. While for students, it can boost their self-esteem to prevent peer pressure, which can lead to internet addiction. With the limitation of this study, further research could be conducted especially on how parents and educators could monitor and control the internet usage, also the effects of internet addiction to students’ mental health.